PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK DAUN Litsea elliptica Blume - Chandra, Pra Panca Bayu; Handayani, Indri Astuti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Kalimantan Island is an area with forests that can be developed for potential results, especially in plants with medicinal properties for health. The medicinal properties of plants are the role of the secondary metabolites contained in them. One of them is Litsea, a plant that comes from the Lauraceae family with 45 genera and more than 2,000 species. Plants from this genus are widely used by the community as traditional medicine, especially Litsea elliptica. One of the secondary metabolite contents of Litsea elliptica is flavonoids. The aim of this research was to determine the flavonoid content of Litsea elliptica leaf extract. The extraction process was carried out by maceration with 96% ethanol solvent. The results of the maceration extraction are then carried out by evaporation until a thick extract is obtained. The total flavonoid content was determined using the Colorimetric-Aluminum Chloride Method with a UV-Vis spectrophotometric instrument, resulting in a total flavonoid content of Litsea elliptica leaf extract of 391.01 mg ± 0.27 mg. The conclusion of this research is that Litsea elliptica leaf extract has a flavonoid content of 0.39%